Pengaruh Pengendalian Internal Dan Gaya Kepemipinan Terhadap Kecenderungan Kecurangan (Fraud) - Fitra Rahmat Sakti; Rahmawati Rahmawati; Rahmad Solling Hamid (Politeknik Ganesha Medan, 2022)
This study aims to examine the effect of Internal Control and Leadership Style on Fraud Tendency. This research is a quantitative research using primary data obtained from questionnaires. The object of this research are employees who work in the Manurung Palopo Cooperative. The sampling technique used a saturated sample. The method of analysis in this study used multiple linear regression analysis using SPSS 22 software. The results showed that internal control and leadership style had a negative and significant effect on the tendency to fraud. Keywords: internal control, leadership style, tendency to fraud